Low dose dobutamine echocardiography for predicting functional recovery after coronary revascularisation. Issue 6 (1st December 2001) - Piscione, F; Perrone-Filardi, P; De Luca, G; Prastaro, M; Indolfi, C; Golino, P; Dellegrottaglie, S; Chiariello, M
Abstract : OBJECTIVE: To evaluate the effects of chronic coronary occlusion on the accuracy of low dose dobutamine echocardiography in predicting recovery of dysfunctional myocardium after revascularisation. DESIGN: Retrospective study. SETTING: Tertiary referral centre. PATIENTS: 53 consecutive patients with ⩾ 70% stenosis of the left anterior descending coronary artery (LAD) and regional ventricular dysfunction (group 1, non-occluded LAD; group 2, occluded LAD) who underwent dobutamine echocardiography. INTERVENTIONS: 26 patients underwent coronary artery bypass grafting and 27 had percutaneous transluminal coronary angioplasty. MAIN OUTCOME MEASURES: Baseline studies before revascularisation included cross sectional echocardiography at rest and during dobutamine infusion (5–10 μg/kg/min), and coronary angiography. The dobutamine study was performed mean (SD) 35 (28) days before revascularisation. Echocardiography at rest was repeated 90 (48) days after revascularisation. RESULTS: Of 296 dysfunctional segments, 63 in group 1 (43%; 63/146) and 69 in group 2 (46%; 69/150) (NS) improved at follow up. Mean (SD) regional wall motion score index decreased from 1.97 (0.48) (95% confidence interval (CI) 1.01 to 2.93) before revascularisation to 1.74 (0.52) (95% CI 0.70 to 2.78) at follow up in group 1 (p = 0.001), and from 2.12 (0.41) (95% CI 1.30 to 2.98) to 1.88 (0.36) (95% CI 1.16 to 2.60) in group 2 (p = 0.0006). In group 1, sensitivity (87% v 52%; p < 0.0001), negative predictive value (88% v 65%; p = 0.001), and accuracy (77% v 64%; p = 0.01) were all significantly higher than in group 2, despite the angiographic evidence of collaterals in patients with occluded vessels. CONCLUSIONS: Dobutamine echocardiography shows reduced sensitivity in predicting recovery of dysfunctional myocardium supplied by totally occluded vessels. Thus caution should be used in selecting such patients for revascularisation on the basis of a viability assessment made in this way.